2017
DOI: 10.1007/s10533-017-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dynamics and phytoplankton community structure: the role of organic nutrients

Abstract: Dissolved organic nitrogen (DON) is recognised as an important N source for phytoplankton. However, its relative importance for phytoplankton nutrition and community composition has not been studied comprehensively. This study, conducted in a typical Scottish fjord, representative of nearpristine coastal environments, evaluates the utilisation of DON and dissolved inorganic nitrogen (DIN) by different microbial size fractions and the relationship of phytoplankton community composition with DON and other parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 113 publications
(125 reference statements)
5
32
1
1
Order By: Relevance
“…Urea and DFAA contributed significantly to the total measured N uptake during blooms (Figs. 3,4,6,7,and 8), consistent with other studies (Glibert et al 2001;Mulholland et al 2002Mulholland et al , 2009aHeil et al 2007;Anderson et al 2008;Gobler et al 2012;Boneillo and Mulholland 2014;Bronk et al 2014;Moschonas et al 2017). We also observed that high rates of DON uptake for these compounds were not limited to periods when there were blooms (Fig.…”
Section: Nitrogen Uptakesupporting
confidence: 92%
See 2 more Smart Citations
“…Urea and DFAA contributed significantly to the total measured N uptake during blooms (Figs. 3,4,6,7,and 8), consistent with other studies (Glibert et al 2001;Mulholland et al 2002Mulholland et al , 2009aHeil et al 2007;Anderson et al 2008;Gobler et al 2012;Boneillo and Mulholland 2014;Bronk et al 2014;Moschonas et al 2017). We also observed that high rates of DON uptake for these compounds were not limited to periods when there were blooms (Fig.…”
Section: Nitrogen Uptakesupporting
confidence: 92%
“…3, 4, and 8). During all years, DIN contributed substantially to N demand during both bloom and non-bloom periods, similar to what has been shown in other estuarine and coastal marine systems (Heil et al 2007;Mulholland and Lomas 2008;Mulholland et al 2009a, b;Boneillo and Mulholland 2014;Bronk et al 2014;Moschonas et al 2017 − was also a quantitatively large source of N to Gymnodinium sp. and other dinoflagellate-dominated phytoplankton communities (Fig.…”
Section: Nitrogen Uptakesupporting
confidence: 82%
See 1 more Smart Citation
“…The ecology of prokaryotes and protists, especially Antarctic phytoplankton during summer (11)(12)(13)(14)(15)(16), together with the major role of viruses in prokaryotes and eukaryotic phytoplankton mortality (17)(18)(19)(20) have been well studied. However, due to the geographical location and the difficulty of culturing viral hosts, an understanding of virus diversity and viral community structures in coastal regions of Antarctica including Sub-Antarctic areas is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, research based on DOM materials extracted by different methods may lead to different results, because various DOM components play different roles in ecological processes. For example, during the microbial degradation of DOM, components rich in N and P (i.e., amino acids and nucleotides) are transformed into inorganic nutrients (i.e., ammonium, nitrate, phosphate) (Moschonas et al, 2017;Brailsford et al, 2017). Low-molecular weight organic acids can improve the transport of metal ions in soil through the formation of metal-organic acid complexes (Wu et al, 2010 as they are less used by microorganisms (Nebbioso and Piccolo, 2013;Cotrufo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%